SECULARISM AND PROBLEMATICS OF FREEDOM OF EXPRESSION IN FRANCE - Wisnu Tri Cahyo; Widi Setyawan (Fakultas Agama Islam Universitas Islam As Syafi'iyah, 2019)
This article is related to the potential of hanphone waqf as a power for the development of the welfare of the people in the distance learning period. Waqf is no longer synonymous with land earmarked for educational institutions, tombs, places of worship or others, but waqf can also be used as a source of strength to realize the welfare of the people in economic empowerment or potential aids. The greater and more diverse the waqf assets that can be managed by nadzir professionally with proper management, the benefits that will be obtained from the management of waqf will be more widely used, thereby increasing the economy and welfare of the people.